DOI: 10.14393/ufu.di.2016.550
|View full text |Cite
|
Sign up to set email alerts
|

Características do gestor, composição das carteiras e desempenho dos fundos multimercados brasileiros

Abstract: This work aims to contribute to the literature on investment funds in emerging markets to address the portfolio composition and performance of Brazilian hedge funds under the manager's perspective. This is because in emerging countries an efficient allocation of assets in the portfolios of the funds is subject to different risk characteristics of the active participants of these portfolios, in addition to the composition of the portfolios be a possible explanation for the differences in performance of the fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
0
5
0
4
Order By: Relevance
“…For example, Borges Júnior and found equivalent results for the relationship between redemption restrictions and Brazilian mutual funds' performance, measured by Sharpe ratio, Sortino ratio and Jensen's alpha. In a previous study about managers characteristics and portfolio composition, Maestri and Malaquias (2018) found no difference in the performance of Brazilian multimarket funds, measured by Sharpe ratio and Sortino ratio. Additionally, Wu et al (2017) evaluated the consistency of European mutual funds' performance in terms of earnings volatility, their results were similar to Sharpe ratio, Jensen's alpha, Sortino ratio and Treynor ratio, besides other measures considered.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…For example, Borges Júnior and found equivalent results for the relationship between redemption restrictions and Brazilian mutual funds' performance, measured by Sharpe ratio, Sortino ratio and Jensen's alpha. In a previous study about managers characteristics and portfolio composition, Maestri and Malaquias (2018) found no difference in the performance of Brazilian multimarket funds, measured by Sharpe ratio and Sortino ratio. Additionally, Wu et al (2017) evaluated the consistency of European mutual funds' performance in terms of earnings volatility, their results were similar to Sharpe ratio, Jensen's alpha, Sortino ratio and Treynor ratio, besides other measures considered.…”
Section: Discussionmentioning
confidence: 75%
“…From a theoretical point of view, this study provides a possible explanation for the equivalent results among different performance measures observed in previous research about funds. Borges Júnior and Malaquias (2019), Maestri and Malaquias (2018) and Wu et al (2017), for example, considered different performance measures and found equivalent results. This study demonstrates, empirically, that Sharpe ratio, Sortino ratio, Jensen's alpha and Treynor ratio are positively correlated, thus explaining the equivalence in the evaluation of funds through different performance measures, verified in the literature.…”
Section: Initially Tablementioning
confidence: 96%
See 3 more Smart Citations